2015
DOI: 10.1016/j.jcrs.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Iris-fixated phakic intraocular lens implantation to correct myopia and a predictive model of endothelial cell loss

Abstract: The authors report no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…Our results are in good agreement with other studies which showed successful refractive results of IF pIOLs implantation [ 7 , 10 , 11 , 14 , 23 , 24 ]. Tahzib et al reported the MRSE −0.7 ± 1.0 D after 10 years, with no significant change in MRSE between 1, 6, and 10 years.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in good agreement with other studies which showed successful refractive results of IF pIOLs implantation [ 7 , 10 , 11 , 14 , 23 , 24 ]. Tahzib et al reported the MRSE −0.7 ± 1.0 D after 10 years, with no significant change in MRSE between 1, 6, and 10 years.…”
Section: Discussionsupporting
confidence: 93%
“…Bouheraoua et al performed a linear model analysis of the 5-year follow-up to present a model that describes endothelial cell loss as a linear decrease. This model predicted that for patients with preoperative ECD of 3000, 2500, and 2000 cells/mm 2 , a critical ECD of 1500 cells/mm 2 will be reached at 39, 28, and 15 years after the implantation, respectively [ 7 ]. Such a model seems to be very useful and helps us to improve the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some researchers have not detected such association, e.g. Bouheraroua et al and Galvis et al [8,16].…”
Section: Discussionmentioning
confidence: 97%